2006
DOI: 10.1007/s00167-006-0165-z
|View full text |Cite
|
Sign up to set email alerts
|

A prospective comparison of bone-patellar tendon-bone and hamstring tendon grafts for anterior cruciate ligament reconstruction in male patients

Abstract: The aim of the study was to compare the results after arthroscopic anterior cruciate ligament (ACL) reconstruction using central-third, bone-patellar tendon-bone (BPTB Group) (n = 45) and four-strand semitendinosus/gracilis (ST/G Group) (n = 78) autografts in male patients. The type of study is non-randomised, prospective consecutive series. A consecutive series of 126 male patients, all with unilateral ACL ruptures, was included in the study. In both groups, interference screw fixation of the graft was used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
7

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 59 publications
(126 reference statements)
5
40
0
7
Order By: Relevance
“…We agree with the literature [5,23] and believe that patellar tendon reconstructions with a standard approach, in which the incision is bigger than in hamstring procedures, should cause more sensory deficits. A bigger sample should confirm this.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We agree with the literature [5,23] and believe that patellar tendon reconstructions with a standard approach, in which the incision is bigger than in hamstring procedures, should cause more sensory deficits. A bigger sample should confirm this.…”
Section: Discussionsupporting
confidence: 91%
“…Afterwards, they were asked to subjectively classify it as impossible, difficult, unpleasant or normal (following the described knee walking test [22,23]). They were also requested to crouch and classify subjectively as possible with pain, possible without pain, or impossible.…”
Section: Methodsmentioning
confidence: 99%
“…Increasingly, the Tegner Activity Scale is used as selfreported by patients, [12,16,19,31] and several recent publications did not describe the collection mode. [4,5,10,15,17,18,29] We could however not find any study supporting the use of the Tegner Activity Scale as a self-reported outcome. Football is represented at three different levels of this scale: 10 is equivalent to national level; 9 to competitive level; and 7 to recreational level.…”
Section: Introductionmentioning
confidence: 65%
“…In the cases with the patellar tendon, femoral fixation was achieved by means of the "press fit" technique: not only is this biological and safe (22,23) , but also it avoids screw deviation or breakage of the posterior cortical boner (17) . Although some authors have reported that patients have returned to a higher activity level with the patellar tendon (24) , Pinczewski (25) did not find any difference in results between the two types of graft, in series with ten years of follow-up. However, because of the lower morbidity from harvesting the flexor tendons, and because of the fewer radiographic abnormalities found in this group, these tendons were indicated as the first choice.…”
Section: Discussionmentioning
confidence: 86%
“…In the patellar tendon group, 26 (96.3%) were very satisfied (24) or satisfied (2), while one patient was dissatisfied. In the flexor tendon group, all the patients were either very satisfied (20) or satisfied (5) (p = 0.99) ( Table 7).…”
Section: Resultsmentioning
confidence: 97%